High capacity cathode materials for lithium ion batteries - Li, Jindan. (2013)
Synthesis and electrochemical studies on LiVO3 nanomaterial as lithium ion battery cathode was investigated. The report covers two methods to produce the LiVO3 as cathode based on the existing methods of making other cathode materials, and by doing some modifications the desired cathode materials will be produced. On top of that, the methods of making the precursors will also be introduced.